Use of Plackett-Burman design for enhanced phytase production by Williopsis saturnus NCIM 3298 for applications in animal feed and ethanol production - Pable, Anupama A.; Shah, Sarah; Kumar, V. Ravi; Khire, Jayant M. (3 Biotech, 2019)
Distiller-dried grain solid (DDGS), a co-product of alcohol production, contains cereal grain residues, proteins, and yeast metabolites, which make it suitable in poultry feeding. However, high phytate content of DDGS limits its applicability in poultry feed. In this study, Plackett-Burman design was used to improve cell-bound phytase production by Williopsis saturnus NCIM 3298, and we achieved an enzyme activity of 269IU/g of dry-wet biomass. The effect of this enhanced phytase-displaying yeast strain on hydrolysis of corn phytate and subsequently on ethanol production and DDGS quality was then investigated. Results of saccharification in the presence of phytase showed that reducing sugar content of liquefied mash increased by 11%, which subsequently improved the ethanol production by 18% (w/v) (p<0.01) compared with the control. Notably, phytase treatment decreased the phytate content of corn by 70% (p<0.01) compared with the control, thereby improving the availability of free phosphate in fermentation broth and DDGS. Thus, the results obtained suggest that the addition of W. saturnus NCIM 3298 strain has the potential of providing a new source of phytase that would be useful in the feed and ethanol industries.
Keywords: DDGS; Ethanol; Phytase; Plackett-Burman Design; Williopsis saturnus NCIM 3298